The Effect of Mind Mapping Media on Group B Storytelling Ability in Ayu Palembang Kindergarten - Sella Oktarina; Taty Fauzy; Mardiana Sari (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2022)
The storytelling method is a fairly effective method given to the golden age of early childhood, as an effort to improve their cognitive, affective and psychomotor functions. The observation results showed that the storytelling ability of Group B children at Ayu Palembang Kindergarten was still low. This study aims to influence the influence of mind mapping media on storytelling skills and at the same time to find out what factors are the causes of low children's storytelling abilities in the learning process at Ayu Palembang Kindergarten. The research approach uses a quantitative pre-experimental method with a one group pre-test post-test design. Sample 14 people. Data collection is done through observation, observation and documentation. Data analysis techniques through normality and homogeneity tests. To see the effect of each variable and answer the research hypothesis, a t test was carried out with a significant (α) 0.05). The findings prove that tcount = 171.92 > ttable = 1,771. The findings answer the hypothesis that mind mapping media has an effect on the storytelling ability of group B children at Kindergarten Ayu Palembang.